A new prenylated coumarin diglycoside with insulin-release promoting activity from Clausena dunniana. Issue 4 (3rd April 2021) - Cao, Nan-Kai; Zhu, Si-Si; Chen, Yue-Mei; Ma, Xiao-Li; Zhao, Ming-Bo; Li, Jun; Tu, Peng-Fei; Jiang, Yong
Abstract: A new prenylated coumarin diglycoside, 6-prenylcoumarin-7- O - β -D-apiofuranosyl-(1→6)- β -D-glucopyranoside (1 ) and five known flavonoid glycosides (2–6 ) were isolated from the leaves and stems of Clausena dunniana . The structures of these isolates were elucidated based on comprehensive MS, UV, IR, and NMR spectroscopic data analysis and comparison with the data reported in literature. Compounds 2–6 are obtained from the title plant for the first time. All these isolates were evaluated for their insulin-release promoting effects, and compounds 1, 2, and 4 exhibited significant activities (2.0 to 3.3-fold higher in comparison with the control, p < 0.01) at 40 μM.